1998
DOI: 10.1159/000014022
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Effects of Breast-Feeding: Does Breast-Feeding Really Matter?

Abstract: Breast-feeding protects the newborn against infectious diseases in developing as well as in industrialized countries. Protection is conferred against gastrointestinal and respiratory tract diseases as well as against otitis media. This protection provided by specific (antibody dependent) and broad, nonspecific protective factors in human milk (proteins, glycoproteins, and lipids) is associated with lower global morbidity and mortality of breast-fed infants as compared with formula-fed infants. While protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 90 publications
(141 reference statements)
1
25
0
3
Order By: Relevance
“…A protective effect of breast-feeding on lymphoma was reported in other studies (Davis et al, 1988;Shu et al, 1995), but the effect was not significant for leukaemia (Davis et al, 1988;Magnani et al, 1988;Shu et al, 1995). Some of the components of breast milk actively stimulate the immune system and promote its development, increasing the capacity of children to face immune challenge (Hasselbalch et al, 1996;Hanson, 1998;Villalpando and Hamosh, 1998). This supports the immunological model proposed by Greaves (1997) and the present results.…”
Section: Discussionsupporting
confidence: 89%
“…A protective effect of breast-feeding on lymphoma was reported in other studies (Davis et al, 1988;Shu et al, 1995), but the effect was not significant for leukaemia (Davis et al, 1988;Magnani et al, 1988;Shu et al, 1995). Some of the components of breast milk actively stimulate the immune system and promote its development, increasing the capacity of children to face immune challenge (Hasselbalch et al, 1996;Hanson, 1998;Villalpando and Hamosh, 1998). This supports the immunological model proposed by Greaves (1997) and the present results.…”
Section: Discussionsupporting
confidence: 89%
“…Several case -control studies found a negative correlation between frequency and duration of breast-feeding and type 1 diabetes (Schrezenmeir & Jagla, 2000;Villalpando & Hamosh, 1998). This beneficial action has been attributed to reduced exposure to diabetogenic agents (especially viruses).…”
Section: Lcpufas and Type 1 Diabetesmentioning
confidence: 99%
“…The major components in formula milk are similar to breast milk, but breast milk contains many additional factors (Villapando & Hamosh, 1998;Bernt & Walker, 1999), and is the best form of nutrition for the infant. Currently, there is little information on the levels of lutein and zeaxanthin in human milk and none in formula milk.…”
Section: Introductionmentioning
confidence: 99%